Performance of chest radiograph and CT scan for lung cancer screening in asbestos-exposed workers. Issue 8 (8th March 2009) - Clin, B; Morlais, F; Guittet, L; Gislard, A; Marquignon, M-F; Paris, C; Caillard, J-F; Launoy, G; Letourneux, M
Abstract : Objectives: The aim was to compare, in a cohort of asbestos-exposed workers, the sensitivity and the specificity of low-radiation helical chest CT scan with chest radiograph for the biennial screening of bronchopulmonary cancer, according to the size of detected nodules. Material and methods: The screening procedure consisted of biennial chest radiograph and monodetector chest CT scan, given to 972 individuals who had been highly exposed to asbestos. A total of 2555 screening procedures were performed. The study focuses on the 1230 screening procedures for which a 2-year follow-up period was available. Results: Twenty-four cases of bronchopulmonary cancer were diagnosed. CT scan detected 20 cancers, 12 of which had not been detected by chest radiograph. Sensitivity of chest radiograph and CT scan were, respectively, 33% and 83%, lesions measuring over 2 mm in diameter being considered as suspect. The specificity of chest radiograph and CT scan were, respectively, 95% and 78%. Calculation of the differential false positive/true positive (FP/TP) ratio and the receiver operating characteristic curve, performed for both chest radiograph and CT scan, facilitated the determination of the best possible compromise between specificity and sensitivity, according to the diameter threshold applied for considering a nodule as suspect. Conclusions: Although this study confirms the superior sensitivity of chest CT scan compared with conventional chest radiograph, the associated loss in specificity leads to a recommended diameter of 5 mm as the threshold for considering non-calcified lesions as "suspect", for the surveillance of asbestos-exposed individuals.